Avoiding immunogenic drugs is key to preserve renal function in patients receiving immune checkpoint inhibitors: Lessons learned from three illustrative cases. Issue 3 (October 2021) - Martínez Valenzuela, Laura; Antón, Paula; Tango, Ariel; Gómez, Francisco; Fulladosa, Xavier; De Carvalho, Alejandra; Gomà, Montserrat; Cruzado, Josep Maria; Draibe, Juliana; Torras, Juan
Background: In the recent years, new immunotherapy agents are showing promising results in the treatment of cancer. Immune checkpoint inhibitors (ICI), which block neoplasm-induced lymphocyte inhibition and enhance cancer immunosurveillance mechanisms, are associated to acute tubulointerstitial nephritis (ATIN). The mechanisms of this adverse effect are debated. Methods: We present a three-case series of ATIN in the setting of ICI therapy managed in our Nephrology department. We detail the clinical course of the episodes, emphasizing on the concomitant medications administered. We also conducted a literature review of the altered drug immunogenicity in patients under immunotherapy drugs. Results: The three reported ATIN cases illustrate closer temporal association with the concomitant medication rather than the ICI itself. This suggests a scenario where the tolerance to previously accepted drugs seems to be lost. Moreover, one of the patients presented an ATIN flare after ICI discontinuation, suggesting an state of leukocyte hyperactivation. Conclusions: Unraveling the exact patho-mechanisms by which ICI-related ATIN occurs will allow the prevention of the development of this side effect and determine whether ICI re-challenge in patients previously affected by ICI-ATIN is safe.